When tumor doesn’t read textbook. Third case of TTF1 and p40 co-expression in the same tumour cells in a non-small cell carcinoma. A potential new entity to consider? - Spinelli, M.; Khorshad, J.; Viola, P. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
Introduction. The 2011 WHO Classification for lung adenocarcinoma enlightened the need for a wise use of immunohistochemistry to preserve tissue for both diagnosis and molecular studies. The current recommendation is to use a panel comprising TTF1 and p40 to classify tumors with no clear squamous or glandular differentiation as many studies have showed the higher specificity of p40 over p63 as marker of squamous differentiation. However, the co-expression of both markers opens a new scenario with subsequent classification and potentially treatment issues. Materials and methods. We report a case of a non-small lung cell carcinoma (NSCLC) with coexistent expression of TTF1 and p40 in the same tumour cells. To our knowledge, this peculiar immunohistochemical profile is very rare, and thus a review of the clinical and molecular features including molecular variances of the tumour was performed. Review of the pertinent literature was also carried out. Results. Two additional articles describing unusual cases of NSCLC with coexistent expression of TTF1 and p40 were found and compared to our case. Interestingly, they all carried out aberrant mutation in TP53 oncogene and were of advance stage. Conclusion. The positivity for both “squamous” and “adenocarcinomatous” markers and mutations of TP53 could be the expression of a not fully recognized variant of NSCLC with possible implications for classification, diagnosis and therapy.